A new 4’,6-dihydroxy,4-methoxybenzophenone-2-O-β-D-gentiobioside and 4’,6-dihydroxy,4 methoxybenzophenone-2-O-β-D-glucoside isolated from methanolic extract of Phaleria macrocarpa (Scheff.) Boerl leaves - Yosie Andriani; Effendy AWM; Tengku Sifzizul Tengku Muhammad; Habsah M; Jalifah Latip (International Journal of Phytomedicine, 2014)
A new 4’,6-dihydroxy,4-methoxybenzophenone-2-O-β-D-gentiobioside (1) was obtained from the leaves of Phaleria macrocarpa (Scheff.) Boerl along with known 4’,6-dihydroxy,4-methoxybenzophenone-2-O-β-D-glucoside (2). Bioactivity assays indicated that compound (1) and (2) have antioxidant activity and enhancement on SR-B1 genes expression in vitro. Their structures compounds were established by the interpretation of their spectroscopic data and comparison with known compounds.